Comparison of Contrasting Method Based on Local Contrast Measurement - Nahlik, Tomas (Communications - Scientific letters of the University of Zilina, 2017)
Some biological experiments and techniques, especially electron microscopy, require special sample treatments. These treatments usually change the samples and biologist cannot apply different techniques on the very same sample. In this case, it is necessary to have some comparison method to compare different treatments. In the electron microscopy, the heavy metals are used as contrasting chemicals. Question is which contrasting method is the best or which is better for imaging of given samples. Standard method is based on visual comparison and it is user dependent. We propose to measure local contrast and some other values like SNR (Signal-to-Noise Ratio), histograms, intensity profiles on the borders of the object and calculate statistical values for pixels’ intensities.